Translocation of Phytoliths Within Natural Soil Profiles in Northeast China - Liu, Lidan; Li, Dehui; Jie, Dongmei; Liu, Hongyan; Gao, Guizai; Li, Nannan (Frontiers in Plant Science, 2019)
Phytoliths are a reliable paleovegetation proxy and have made an important contribution to paleoclimatic studies. However, little is known about the depositional processes affecting soil phytoliths, which limits their use for paleoclimate and paleovegetation reconstructions. Here, we present the results of a study of the vertical translocation characteristics of phytoliths in 40 natural soil profiles in Northeast China. The results show that phytolith concentration decreases within the humic horizon of the soil profiles and that ~22% of the phytoliths are translocated below the surface of the studied soils. In addition, we found that the translocation rate of phytoliths varies markedly with phytolith type, and that phytolith size and aspect ratio also have a significant effect. Phytoliths with length>30μm and with aspect ratio>2, and those with length<20μm and aspect ratio<2, are preferentially translocated compared to those with length >25 μm and aspect ratio<2. Our results demonstrate that differential translocation of phytoliths within soil profiles should be considered when using soil phytoliths for paleoclimate and paleovegetation reconstruction.